Impact of a Pretreatment Step on the Acidogenic Fermentation of Spent Coffee Grounds - Joana Pereira; Marcelo M. R. de Melo; Carlos M. Silva; Paulo C. Lemos; Luísa S. Serafim (Bioengineering, 2022)
Acidogenic fermentation (AF) is often applied to wastes to produce short-chain organic acids (SCOAs)—molecules with applications in many industries. Spent coffee grounds (SCGs) are a residue from the coffee industry that is rich in carbohydrates, having the potential to be valorized by this process. However, given the recalcitrant nature of this waste, the addition of a pretreatment step can significantly improve AF. In this work, several pretreatment strategies were applied to SCGs (acidic hydrolysis, basic hydrolysis, hydrothermal, microwave, ultrasounds, and supercritical CO2 extraction), evaluated in terms of sugar and inhibitors release, and used in AF. Despite the low yields of sugar extracted, almost all pretreatments increased SCOAs production. Milder extraction conditions also resulted in lower concentrations of inhibitory compounds and, consequently, in a higher concentration of SCOAs. The best results were obtained with acidic hydrolysis of 5%, leading to a production of 1.33 gSCOAs/L, an increase of 185% compared with untreated SCGs.